2009
DOI: 10.1016/j.freeradbiomed.2009.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Signaling events in apoptotic photokilling of 5-aminolevulinic acid-treated tumor cells: Inhibitory effects of nitric oxide

Abstract: Antitumor photodynamic therapy (PDT) employs a photosensitizing agent, molecular oxygen, and visible light to produce reactive oxygen species that can destroy tumor and tumor vasculature cells. NO produced by these cells could be pro-carcinogenic by inhibiting apoptosis and promoting angiogenesis and tumor growth. We recently showed that NO from a chemical donor or activated macrophages makes COH-BR1 breast tumor cells more resistant to photokilling sensitized by 5-aminolevulinic acid (ALA)-generated protoporp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 63 publications
4
67
0
1
Order By: Relevance
“…When an iNOS inhibitor (1400W) or NO scavenger (cPTIO) was used, it was introduced 30 min before ALA and maintained at the same concentration throughout irradiation and post-irradiation incubation. Immediately after ALA treatment, cells were switched to fresh medium either lacking or containing iNOS inhibitor or NO scavenger, and then irradiated on a translucent plastic platform over a bank of four 40-W cool-white fluorescent tubes [22]. The intensity (fluence rate) of light reaching the bottom surface of culture dishes was ~11 W/m 2 , as measured with a YSI radiometer (Yellow Springs, OH).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When an iNOS inhibitor (1400W) or NO scavenger (cPTIO) was used, it was introduced 30 min before ALA and maintained at the same concentration throughout irradiation and post-irradiation incubation. Immediately after ALA treatment, cells were switched to fresh medium either lacking or containing iNOS inhibitor or NO scavenger, and then irradiated on a translucent plastic platform over a bank of four 40-W cool-white fluorescent tubes [22]. The intensity (fluence rate) of light reaching the bottom surface of culture dishes was ~11 W/m 2 , as measured with a YSI radiometer (Yellow Springs, OH).…”
Section: Methodsmentioning
confidence: 99%
“…2.3 and then either not irradiated (dark control) or irradiated (~1 J/cm 2 ). Cell lysates were prepared as described [21,22], analyzed for total protein, then subjected to Laemmli SDS-PAGE, using 15% acrylamide/bis-acrylamide. Separated proteins were transferred to a polyvinyidene difluoride membrane and, after blocking, the membrane was incubated overnight at 4 °C with an iNOS, TIMP1, TIMP-2, integrin α6, or integrin β1 antibody at a supplier-recommended dilution.…”
Section: Methodsmentioning
confidence: 99%
“…Di Venosa et al 19 , however, did not observe any relationships between NO production and photodynamic cell injury. The cytoprotection, anti-apoptotic effect of NOS in 5-aminolevulinic-mediated PDT of both murine tumor and normal cells, has been reported 20 , and iNOS was shown to play the leading role in it 21 . Another view was suggested by Lu et al 22 : the authors suppose that mitochondrial NOS and following cytochrome c release play the leading role is PDT induced cell damage, in particular, in the case of cancer cells.…”
Section: Discussionmentioning
confidence: 95%
“…NO produced by photosensitized cells could be pro-carcinogenic by inhibiting apoptosis. It was shown that NO from chemical donor or activated macrophages made breast tumor cells sensitized by 5-aminolevulinic acid-generated protoporphyrin IX more resistant to photo killing by providing substantial protection against apoptosis [39,40] . Additionally, it was demonstrated that PDT-treated breast cancer cells acquired the ability to upregulate inducible-nitric oxide synthase (iNOS) expression [41] .…”
Section: Pdt and Nitric Oxide (No) Scavengersmentioning
confidence: 99%